Importance of jewelry in Women: Case Study in Pakistan - Syeda Sadia Afzal (Borong Newinera Publisher, 2020)
Jewelry’s anecdotes have been growing up since kingdom times. Getting acceptation day by day, women are using jewelry cutturely, etiquette generation and acquiesce. Passion of jewelry in women has trending now a days, another trending of young generation to become more attractive and beautiful with the help of jewelry. Everyone use jewelry for their capacity like, Diamon, Gold, Silver, Pearls and other materials. Time is changed and the importance of jewelry has been increased, Gold and Silver’s values are different but getting expensive of Gold other material take place here some other introduction of jewelry.